Internet of Things: a comprehensive overview, architectures, applications, simulation tools, challenges and future directions - Anita Choudhary (Discover Internet of Things)
Abstract In recent years, Internet of Things (IoT) evolved as a new paradigm and gained a lot of traction in the wireless telecommunications industry. It changed the traditional way of living into a high-tech lifestyle through the integration of intelligent devices, applications, and technologies that automate everything around us. The IoT is anticipated to connect physical objects to facilitate intelligent decision making in the future years. Several studies have been conducted to improve IoT technology. To fully realize the potential of IoT, numerous problems and issues remain to be addressed. IoT challenges and issues must be addressed from multiple perspectives, including applications, supporting technology, and social and environmental implications. This review paper aims to provide a full discussion from both technological and social perspectives. The paper highlights several challenges and critical aspects in IoT, architecture, and its application fields. A generic architecture of IoT is proposed with its enabling technologies to highlight the uses of each layer and technologies that implemented in it. Market opportunities are a highlight that helps to understand the growth of IoT. Further, the functional blocks and working of IoT is discussed, so the researchers take interest in its implementation. Also, a detailed discussion on IoT fields and it’s uncovered challenges are highlighted. A brief overview of existing simulators and their functionalities is discussed, so that researchers can easily select the simulator as per their targeted objectives. In addition, major issues are highlighted that should be addressed by the scientific community. Finally, the significance of this research is to understand fundamentals of IoT architecture as well as a complete review in order to delve deeper into the difficulties and devise appropriate solutions.